Predictive Value of Early A-EEG in HIE Outcome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
Researchers at Wayne State University and other US Pediatric Centers examined the predictive value of the early amplitude integrated electroencephalogram (aEEG) and stage of encephalopathy among infants with hypoxic-ischemic encephalopathy (HIE) eligible for whole-body hypothermia.